Pengaruh Two Step Annealing pada Struktur Kristal Nanopartikel Cobalt Ferrite Hasil Ko-presipitasi: Chomsatin Amalia, Suharyana, Budi Purnama - Chomsatin Amalia, Chomsatin Amalia; Suharyana, Suharyana; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Two step annealing dependence on crystal structure in co-precipitated cobalt ferrite nanoparticles have been examined. The FTIR results showed that the cobalt ferrite spinel structure was observed at k = 590 cm-1. Treatment of pre-heating temperature has lowered transmittance and has not shifted wave numbers of cobalt ferrite vibration. Confirmation of crystalline structure using XRD indicated that fcc cobalt ferrite was seen at diffraction peak of 2O = 35,70. Scherer analysis showed that pre heating treatment can modify crystal size of cobalt ferrite sample.